In Conversation : Intention and Innovation in Eighteenth-Century Display - Holmes, Mary Tavener, (Early Modern History and Modern History E-Books Online, Collection 2025., 2026)
At the beginning of the eighteenth century, a generation of collectors in France and the Holy Roman Empire developed new principles for the display of paintings, principles based on comparison triggered by the mixture of schools and periods; its aim was to encourage analysis and connoisseurship through comparison and conversation. The ground-breaking theories of Roger de Piles were central to this novel approach, and essential to its understanding. These principles were predominant until the 1780s. This book examines case studies in France, the German Empire and the UK that exemplify these new principles.